Administrasi Hubungan Kerjasama Sekolah dan Masyarakat - Muhammad Rayya Nur Ramadhan; Muh Reza Wahyudin; M. Fauzan Fahmi; Maman A Majid Binfas; Cita Audia; Muhammad Rif’ah (Departement of Mathematics Education, 2023)
A strong school-community partnership is the foundation for realizing quality education. This colaboration will benefit students, teaching staff, and the wider community. This research aims to learn more about the process, purpose and benefits of community and school collaboration. With a literature approach, this research uses qualitative methods. As a result, to achieve its goals and vision and mission, the school needs a good working relationship with the community. Harmonized school and community collaboration will provide benefits to the community, especially parents. School perfomance determines the level of community trust the school. The community will feel the need to involve themselves in school programs, when all data and information from the school has been delivered and can be understood by the community as a whole. This is obtained through the administrative process of a good and harmonius working relationship